2016
DOI: 10.1139/gen-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Molecular taxonomic analysis of the plant associations of adult pollen beetles (Nitidulidae: Meligethinae), and the population structure ofBrassicogethes aeneus

Abstract: Pollen beetles (Nitidulidae: Meligethinae) are among the most abundant flower-visiting insects in Europe. While some species damage millions of hectares of crops annually, the biology of many species is little known. We assessed the utility of a 797 base pair fragment of the cytochrome oxidase 1 gene to resolve molecular operational taxonomic units (MOTUs) in 750 adult pollen beetles sampled from flowers of 63 plant species sampled across the UK and continental Europe. We used the same locus to analyse region-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 81 publications
2
18
0
Order By: Relevance
“…Pollen beetles often feed on early spring-flowering plants before they move onto oilseed rape (Free and Williams 1978;Ouvrard et al 2016), and have been observed on the crop at pre-green bud growth stages (Veromann et al 2012); during most seasons, it seems that the beetles arrive sufficiently early to colonise even the most advanced crops before the susceptible green bud stages are over (Cook et al 2006;Mauchline et al 2017a). Relative differences in growth stage, for example between a crop and trap crop or variation within a field, however, are very important in determining infestation levels, because of the beetle's preference for the flowering growth stages (Cook et al 2007;Mauchline et al 2017a), which may provide a reliable cue for the availability of buds of the preferred size for oviposition (2-3 mm; Ekbom and Borg 1996), together with food resources (Frearson et al 2005).…”
Section: Sowing Date and Growth Stage Profilementioning
confidence: 99%
See 2 more Smart Citations
“…Pollen beetles often feed on early spring-flowering plants before they move onto oilseed rape (Free and Williams 1978;Ouvrard et al 2016), and have been observed on the crop at pre-green bud growth stages (Veromann et al 2012); during most seasons, it seems that the beetles arrive sufficiently early to colonise even the most advanced crops before the susceptible green bud stages are over (Cook et al 2006;Mauchline et al 2017a). Relative differences in growth stage, for example between a crop and trap crop or variation within a field, however, are very important in determining infestation levels, because of the beetle's preference for the flowering growth stages (Cook et al 2007;Mauchline et al 2017a), which may provide a reliable cue for the availability of buds of the preferred size for oviposition (2-3 mm; Ekbom and Borg 1996), together with food resources (Frearson et al 2005).…”
Section: Sowing Date and Growth Stage Profilementioning
confidence: 99%
“…Meligethes aeneus) (Coleoptera: Nitidulidae), a key pest of oilseed rape Brassica napus L. (OSR), a crop widely grown for cooking oil and biofuel use (EU production 19.8 M tonnes in 2016;Eurostat 2017); in this case, beetle resistance to pyrethroid insecticides, which are often applied prophylactically, has become a major problem (Zimmer et al 2014;Thieme et al 2010). Adult beetles emerge in early spring from overwintering habitats in woodlands and grassy areas (Rusch et al 2012;Blazejewska 1958;Müller 1941), and feed on the flowers of many different plants before seeking OSR crops and other brassicas at the green bud growth stage, for further feeding and oviposition (Free and Williams 1978;Ouvrard et al 2016). Feeding damage causes OSR flower bud abscission, leading to often extensive yield losses (Zlof 2008) that can approach 80% (Hansen 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is the first behavioural process in the pollen beetle life cycle that is known to be strongly influenced by semiochemical cues (reviewed by Williams and Cook 2010). Overwintered adult pollen beetles are generalist feeders on pollen from many different plant families to obtain nutrients for energy (Roulston and Cane 2000) and ovary maturation Ouvrard et al 2016). Pollen beetles locate their food host-plants, which include Brassicas, using a variety of plant semiochemical and visual cues.…”
Section: Food Host-plant Location (Long Range Cues)mentioning
confidence: 99%
“…Pollen beetles have been found feeding on a wide variety of wild plants Mauchline 2003;Ouvrard et al 2016) and are known to respond positively to whole plant odours from several non-Brassicaceous species including dandelion (Taraxacum officinale L.) (Cook 2000), field bean (Vicia faba L.) (Cook 2000), rye (Secale cereale L.) (Ruther and Thiemann 1997), tomato (Solanum lycopersicum L.) (Ruther and Thiemann 1997) and yarrow (Achillea millefolium L.) (Ruther and Thiemann 1997). Some of the semiochemicals responsible for this attraction have been identified.…”
Section: Food Host-plant Location (Long Range Cues)mentioning
confidence: 99%